A New Targeting - A New Take-Up? Non-take-up of Social Assistance in Germany after Social Policy Reforms - Kerstin Bruckmeier; Jürgen Wiemers (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We present first estimates of rates of non-take-up for social assistance in Germany after the implementation of major social policy reforms in 2005. The analysis is based on a microsimulation model, which includes a detailed description of the German social assistance programme. Our findings suggest a moderate decrease in non-takeup compared to estimates before the reform. In order to identify the determinants of claiming social assistance, we estimate a model of take-up behaviour which considers potential endogeneity of the benefit level. The estimations reveal that the degree of needs, measured as the social assistance benefit level a household is eligible for, and the expected duration of eligibility are the key determinants of the take-up decision, while costs of claiming seem to play a minor role.
Keywords: I38; H31; C15; 330; Non-Take-Up; social assistance; microsimulation; Öffentliche Sozialleistungen; Arbeitsmarktreform; Sozialleistungsempfänger; Mikrosimulation; Schätzung; Deutschland